Sol-gel synthesis of magnesium aluminate and synergistic degradation of Cr(VI) ion by adsorption and photocatalysis - Liu, Miao; Wang, Yi; Wu, Yingjun; Liu, Chunyang; Liu, Xin (Frontiers in Materials, 2023)
A conventional polyacrylamide gel route with the different chelating agents including ethylenediamine tetraacetic acid (EDTA), oxalic acid and salicylic acid have been applied to synthesis the MgAl2O4 nanoparticles with the high adsorption capacity and photocatalytic reduction capacity for the adsorption and reduction of Cr(VI). The phase compositions, microstructure characteristics, optical properties, adsorption capacities and photocatalytic reduction capacities of MgAl2O4 nanoparticles can be effectively regulated by changing the type of chelating agent.The pure phase MgAl2O4 nanoparticles were obtained by using EDTA and oxalic acid as chelating agents, but a small amount of MgO impurity appeared in the MgAl2O4 nanoparticles obtained by salicylic acid as chelating agents, which inhibited the adsorption and photocatalytic reduction ability of MgAl2O4 nanoparticles. The optimal MgAl2O4 content, Cr(VI) initial concentration and pH value were 0.75 mg/L, 100 mg/L and 5, respectively. The photocatalytic reduction capacity of MgAl2O4 nanoparticles obtained by oxalic acid as chelating agents was 3.56 times that of MgAl2O4 nanoparticles obtained by salicylic acid as chelating agents. The high adsorption capacity of MgAl2O4 nanoparticles is mainly due to electrostatic adsorption, while the high photocatalytic reduction capacity is mainly due to the high reduction capacity of active free radicals generated by the conduction electrons and valence band holes of MgAl2O4 nanoparticles.